The African football in Europe: Portugal and France’s cases as migratory destination of their former colonies’ players - Melo, Lucas Martins Santos (2018)
One of the characteristics of the African Diaspora is the voluntary movement of people to new regions, where there is usually a demand for specific labor. As football is one of the most specific occupations in the world, and given the increasing amount of African players working in the major centers of football, we have decided to make a brief research to assess this relation between Diaspora and football. In this way, we chose two countries that have an extensive football immigrant community. We refer to the cases of Portugal and France, countries that have adopted the assimilationism, which have had a large set of territories, mainly in Africa, and who profit from the ex-colonies’ labor. This article, based on a scientific literature on the subject and quanti-qualitative data, is intended to show the colonial and neocolonial uses of football undertaken by these countries and to draw a corresponding historical trajectory for such use.